The best strategies don’t just take a long view. They take a broad view - Lang, T; Whittington, R (Harvard Business Publishing, 2022)
Change, speed, uncertainty, disruption, surprise — all are constants in today’s business environment. As a result, leaders who devise strategy can no longer simply plan for what they believe will happen in the long term. Instead, to prepare themselves for the threats and opportunities that can emerge at any moment from any direction, they need to adopt much broader view. In this article the authors explain why taking the broad view of strategy is so important, and they recommend that leaders who want to take the broad view need to think differently in three important ways — by focusing on systems not sectors, scenarios not forecasts, and playbooks not plans.